Legal Protection of Registered Trademark Holders: A Case Study of the Dispute Between PT X and Company Y - Rosalind, Monica; S.T. Kansil, Christine (State of Islamic Institute Langsa, 2025)
Ideally, registered trademark owners receive full legal protection to prevent unauthorized use of their trademarks by other parties. However, in reality, trademark disputes still frequently occur, as seen in the case between PT X and Company Y, highlighting gaps in legal protection for trademark owners. This study aims to analyze legal protection for registered trademark holders and evaluate the effectiveness of regulations in resolving trademark disputes. This article falls under library research with a qualitative approach, utilizing normative legal study methodology. The findings indicate that the trademark dispute between PT X and Company Y underscores the importance of legal protection for registered trademark holders, where the first-to-file registration system grants exclusive rights to the legitimate owner. However, despite existing regulations, disputes persist, necessitating active monitoring and legal enforcement by trademark owners through legal action or dispute resolution in commercial courts.